Le travail du physiothérapeute et sa responsabilité professionnelle - Dumais, Christian N. (Assurances)

(untitled) (HEC Montréal, 1984)
The author studies the duties of physiotherapists, the professional liability claims they face and the protection provided by their errors and omissions insurance policy.